Sweet smell of success [videorecording (DVD)] - Lancaster, Burt, 1913-1994; Curtis, Tony, 1925-2010; Mackendrick, Alexander, 1912-1993 (Vintage classics (MGM Home Entertainment Inc.), 2001)
"A powerful film about a ruthless journalist and an unscrupulous press agent who'll do anthing to achieve success"--Container.